2002
DOI: 10.1182/blood.v99.1.275
|View full text |Cite
|
Sign up to set email alerts
|

The MLL fusion partner AF10 binds GAS41, a protein that interacts with the human SWI/SNF complex

Abstract: The AF10 gene encodes a putative transcription factor containing an N-terminal LAP/PHD zinc finger motif, a functional nuclear localization signal, an AT-hook domain, and a leucine zipper toward the C-terminus. AF10 is involved in 2 distinct chromosomal translocations associated with hematologic malignancy. The chimeric fusion proteins MLL/AF10 and CALM/AF10, resulting from the t(10; 11)(p12;q23) and the t(10;11)(p12;q14), respectively, consistently retain the leucine zipper motif of AF10. This part of the C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 47 publications
0
75
0
Order By: Relevance
“…Another P. C. Abad et al explanation for the effect of NuMA on chromatin structure may be linked to the location of NuMA in the chromatin compartment. In this compartment, NuMA could interact with the putative transcription factor GAS41 (Harborth et al, 2000), a protein shown to bind the chromatin remodeling complex component INI1 (Debernardi et al, 2002). In addition, chromatin-remodeling complexes have been shown to contain actin-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Another P. C. Abad et al explanation for the effect of NuMA on chromatin structure may be linked to the location of NuMA in the chromatin compartment. In this compartment, NuMA could interact with the putative transcription factor GAS41 (Harborth et al, 2000), a protein shown to bind the chromatin remodeling complex component INI1 (Debernardi et al, 2002). In addition, chromatin-remodeling complexes have been shown to contain actin-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…61 In addition, the MLL partner AF10 interacts with the AF9 family member GAS41 which in turn interacts with INI1, also called SNF5. 62 In yeast, SNF5 also interacts with the AF9 family member TGF3. 63 CBP interacts with a newly discovered member of the SWI/SNF complex, SRCAP.…”
Section: Discussionmentioning
confidence: 99%
“…t(11;19), associate and cooperate with SWI/ SNF complexes to activate transcription of the Hoxa7 promoter (Nie et al, 2003). Fusion of MLL to AF10, t(10;11)(p12;23), creates a protein that could interact with GAS41, a member of the basal transcription factor complexes TFIID and TFIIF, and an interacting component of SWI/SNF, and potentially activate Hox gene expression by aberrant chromatin remodelling (Debernardi et al, 2002). Intriguingly, dimerisation of the truncation Figure 1A, are integrated into nucleosomes by a yet not understood mechanism.…”
Section: Aberrant Gene Activation and Cancermentioning
confidence: 99%